232k views
21 votes
Problem 0: Compute the inverse Laplace Transforms of:


F(s) = (s + 1)/(s(s - 1)(s - 3))


F(s) = (1)/((s - 1)(s - 2)(s - 3))



Problem 0: Compute the inverse Laplace Transforms of: F(s) = (s + 1)/(s(s - 1)(s - 3)) F-example-1
User BurtK
by
5.4k points

1 Answer

13 votes

Decompose each given F(s) into partial fractions.


F(s) = (s+1)/(s(s-1)(s-3))

has partial fraction decomposition


(s+1)/(s(s-1)(s-3)) = \frac as + \frac b{s-1} + \frac c{s-3}

Combine the rational terms on the right and solve for the coefficients:


(s+1)/(s(s-1)(s-3)) = (a(s-1)(s-3) + b s(s-3) + c s(s-1))/(s (s-1) (s-3))


1 = a(s-1)(s-3) + bs(s-3) + c s(s-1)


1 = 3 a + (-4 a - 3 b - c) s + (a + b + c) s^2


\begin{cases}3a=1 \\ -4a-3b-c = 0 \\ a+b+c=0 \end{cases} \implies a=\frac13, b=-\frac12, c=\frac16

Then


F(s) = \frac13 * \frac1s - \frac12 * \frac1{s-1} + \frac16 * \frac1{s-3}

Using the frequency-shifting property, the inverse transform is


\boxed{f(t) = \frac13 - \frac{e^t}2 + \frac{e^(3t)}6}

The other transform can be dealt with in the same manner.


F(s) = \frac1{(s-1)(s-2)(s-3)} = \frac a{s-1} + \frac b{s-2} + \frac c{s-3}


\implies 1 = a(s-2)(s-3) + b(s-1)(s-3) + c(s-1)(s-2)


\implies 1 = 6 a + 3 b + 2 c + (-5 a - 4 b - 3 c) s + (a + b + c) s^2


\implies \begin{cases}6 a + 3 b + 2 c=1 \\ -5a-4b-3c = 0 \\ a+b+c=0\end{cases} \implies a=\frac12, b=-1, c=\frac12


\implies F(s) = \frac12 * \frac1{s-1} - \frac1{s-2} + \frac12 * \frac1{s-3}


\implies \boxed{f(t) = \frac{e^t}2 - e^(2t) + \frac{e^(3t)}2}

User Maxim Tulupov
by
5.7k points